(untitled) (Fiep Bulletin - online, 2011)
This article analyzes the relationships between female body, health and fashion, reflecting upon the influence of fashion not only on clothing, but also on female aesthetics from the 19th century to the 21st century. Through a literature review, we attempt to understand how medicine has related fashion and health, how the female body has been treated throughout history, and the consequences of such treatment.